Blackfoot Challenge: better communities through cooperation - Duvall, Ali, author; Stone, Jim, author (Colorado State University. Libraries, 2009)
Since 1993, the landowner-based watershed group the Blackfoot Challenge has been working with public and private partners to coordinate efforts to conserve and enhance the natural resources and rural way of life in the Blackfoot watershed of western Montana. Three phrases guide the Blackfoot Challenge – communication, cooperation and common ground. Through focusing on the 80% that folks can agree on, and not the 20% that divides, this group manages to build trust and relationships to keep working landscapes intact, conserve water to benefit agriculture, fisheries, water quality and habitat, maintain forest health, manage noxious weeds across fence lines, reduce human-wildlife conflicts, and connect classrooms and communities through place-based education. For more information, please see http://www.blackfootchallenge.org/.
Challenges, successes, and opportunities of rancher coalitions: the Blackfoot Challenge
Presented at the Bridging the gap: collaborative conservation from the ground up conference, September 8-11, 2009, Colorado State University, Fort Collins, Colorado, sponsored by the Center for Collaborative Conservation, https://collaborativeconservation.org/. This conference brought together people with experience working collaboratively to achieve both conservation and livelihood goals in tribal nations, rangelands, forests, watersheds, agricultural lands, and urban areas. Ali Duvall is affiliated with Blackfoot Challenge. Jim Stone is affiliated with Rolling Stone Ranch and Blackfoot Challenge.
Keywords: Blackfoot River Valley; collaborative conservation; Blackfoot Challenge; Blackfoot Watershed